KORELASI ANTARA MOTIVASI DENGAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN TEMATIK KELAS V SEKOLAH DASAR MUHAMMADIYAH II PONTIANAK SELATAN - Farah Nabila; Budiman Tampubolon; Tahmid Sabri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis research aimed to determine the relationship between learning motivation andlearning outcomes for class 5 of Elementary School of Muhammadiyah II, PontianakSelatan. The research method used was descriptive quantitative with a form ofcorrelation study research. The population in this research was the fifth-gradestudents of Muhammadiyah II Primary School, Pontianak Selatan. The researchsample was determined by probability sampling technique with random samplingtype and selected the class 5A of Elementary School of Muhammadiyah II, PontianakSelatan. The sources of data in this research were students of class 5A of ElementarySchool of Muhammadiyah II, Pontianak Selatan, and documents of the average dailytest scores. The data was the score of the learning motivation questionnaire and theaverage daily test score. The results showed that 76.64% of students' learningmotivation was in a good category, and 89.92% of the learning outcomes were inthe very good category. The correlation between learning motivation and learningoutcomes obtained results of 0.395 included in the low category.Keywords: Correlation, Learning Motivation, and Learning hypothesis